Cost of sovereign default: Theory and empirical evidence - Ramírez Daza, Ezequiel Fernando (2022)
In this scientific article, the issue of the economic costs that a country assumes by failing to service the public debt, specifically the external public debt, will be addressed. The main costs, on which there is consensus in the literature, are the following: on the economic growth; on the reputation of the sovereign, which generally implies a significant decrease in its international credit ratings and an increase in its financing costs measured by the sovereign credit spread; in international trade they are associated with the greater difficulty that the country's companies have in accessing international bank credit for their commercial operations; Finally, if we consider the impact on the holders of the domestic public debt of a sovereign default event, whose key economic agent is the financial system, then the possibility of a banking crisis or a credit crunch must be considered as a worthy special case. Each of these costs is evaluated with a representative study of the empirical literature, and complemented with other studies, presenting their results. The article ends with the main conclusions drawn from the studies under review, with a personal appreciation and bibliographical references.